Efforts to Increase Student Learning Engagement through the Potential of Token Economy - Khoiriyah, Wahyuna; Mu'awanah, Mu'awanah; Khotimah, Husnul; Janah, Miftahul; Hasanah, Imroatul (Edudeena : Journal of Islamic Religious Education, 2025)
Student engagement is a crucial component of effective learning. A token economy is one strategy that can be utilized to enhance student learning engagement. This study aimed to investigate the difference in average student engagement between an experimental class using a token economy and a control class in Aqidah Akhlak (Islamic Creed and Morals) subject at MTs Hasan Muchyi Kediri. It also sought to determine the magnitude of this difference. This quantitative quasi-experimental study employed a posttest-only control group design. Two classes were selected as research samples: a control class and an experimental class that implemented a token economy. Data were collected using questionnaires and token recording documentation. The questionnaire data were then analyzed using an independent-samples t-test. The results indicate that the use of a token economy significantly impacts student engagement. This conclusion is supported by a significance value of 0.02 < 0.05, demonstrating a significant difference in the average student engagement between the experimental and control classes. The test results also revealed that the average student engagement in the control class was lower than in the experimental class, with a difference of 3.37. Thus, there is a significant difference in the average engagement of seventh-grade students in Aqidah Akhlak at MTs Hasan Muchyi Kediri between the experimental class using a token economy and the control class, with the experimental class exhibiting higher average engagement.